Description of a new species of Pseudopaludicola Miranda-Ribeiro, 1926 from the state of São Paulo, Southeastern Brazil (Anura, Leiuperidae) - Toledo, Luís Felipe (Zootaxa, 2010)
I describe here a new species of Pseudopaludicola (P. serrana) found in the southern limits of the Espinhaço mountain range in the state of Minas Gerais, Brazil. This new species is related to P. saltica and P. murundu and can be diagnosed by the following combination of characters: (1) long hindlimbs and absence of T-shaped terminal phalanges, (2) single, dark, and subgular vocal sac with dark longitudinal folds in males; (3) immaculate to light brown, nuptial pads in males that cover the external part of finger I; (4) SVL/HL greater than 2.7; and (5) advertisement call with dominant frequency above 5 kHz, pulse duration range between 13 and 23 ms, and mean interval between notes of 177 ms. Tadpoles and the advertisement call are also described.